The Nexuses Between Social Media Marketing Activities and Consumers’ Engagement Behaviour: A Two-Wave Time-Lagged Study - Shang, Yunfeng; Rehman, Hina; Mehmood, Khalid; Xu, Aidi; Iftikhar, Yaser; Wang, Yifei; Sharma, Ridhima (Frontiers in Psychology, 2022)
This study examined how social media marketing activities influence consumers' engagement behaviour in developing countries. Based on the stimulus-organism-response theory, we examined the effect of social media marketing activities on consumers' engagement intention and further investigated the moderating effect of social media sales intensity. The study employed a time-lagged design with two waves to confirm the hypothesized framework. The study findings showed that social media marketing activities positively influence consumers' engagement intention and engagement behaviour. In addition, social media sales intensity strengthens the link between engagement intention and engagement behaviour. This study adds to the literature on social media and discusses its practical implications.